2020
DOI: 10.1515/cclm-2020-0931
|View full text |Cite
|
Sign up to set email alerts
|

Association of kidney function with effectiveness of procalcitonin-guided antibiotic treatment: a patient-level meta-analysis from randomized controlled trials

Abstract: ObjectivesPatients with impaired kidney function have a significantly slower decrease of procalcitonin (PCT) levels during infection. Our aim was to study PCT-guided antibiotic stewardship and clinical outcomes in patients with impairments of kidney function as assessed by creatinine levels measured upon hospital admission.MethodsWe pooled and analyzed individual data from 15 randomized controlled trials who were randomly assigned to receive antibiotic therapy based on a PCT-algorithms or based on standard of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…To our knowledge, this is the first analysis addressing the effects of PCT guidance in patients within different age group. There is some overlap with previous secondary reports from the same database particularly regarding description of trials and methodology used for analysis [ 21 , 22 , 28 , 34 , 35 ]. The focus on age groups regarding effects of PCT use, however, is novel and has not been done in previous reports.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To our knowledge, this is the first analysis addressing the effects of PCT guidance in patients within different age group. There is some overlap with previous secondary reports from the same database particularly regarding description of trials and methodology used for analysis [ 21 , 22 , 28 , 34 , 35 ]. The focus on age groups regarding effects of PCT use, however, is novel and has not been done in previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…Still, it remains unclear whether data from these trials are also true for older patients who might have a different cytokine and biomarker response to infection compared to younger patients [ 26 , 27 ]. Older patients may have often impairment in kidney function, which may affect biomarker kinetics, but has not been shown to impact on PCT-guided stewardship efforts in a previous analysis [ 28 ]. Also, older patients have a less pronounced immune response to infection and important differences in regard to the adaptive and innate immunity have been well documented [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, extensive variation in observed biomarker dynamics remains a major challenge limiting further use of PCT as treatment response biomarker in patients with severe infections and sepsis. Such variability is associated with differences in underlying microbial etiologies, comorbidities, 82 and antibiotic treatments. All together, these factors make it more challenging to interpret and evaluate PCT biomarker time course data.…”
Section: Case Study: Procalcitonin To Quantify Antibiotic Treatment Response In Sepsismentioning
confidence: 99%
“…Repeated PCT concentration assessment can be used to monitor the therapeutic response to guide medical decisions on early discontinuation of antibiotics and support personalized antibiotic management [ 2 , 3 ]. Multiple studies have shown that PCT-guided antibiotic initiation and discontinuation can shorten the duration of antibiotic treatment, which can in turn reduce the associated side effects and improve clinical outcomes [ 4 - 7 ]. Recently, two medical decision points have been suggested for PCT-guided antibiotic stewardship: 0.25 and 0.50 μg/L for non-intensive care unit (ICU) and ICU patients, respectively [ 2 ].…”
mentioning
confidence: 99%